Prevention measures for erosion risks and mass removal phenomena, "Ciudad Arcángel" incidence area, Ibarra Cantón, Ecuador - Valles Peralta , Galo Vinicio; Villalba Calderón, Diego Ramiro; Moncada Rangel, José Alí; Guzmán Paz, José Raúl (SATHIRI, 2022)
Risk management allows to reduce, prevent, prepare, respond, achieve recovery, reconstruction, and joint actions aimed at the population and public and private infrastructure safeguarding their integrity in a territory. The aim of the study was to propose prevention measures against erosion risks and mass removal phenomena in the “Ciudad Arcángel” incidence area, Ibarra, Imbabura province. A survey was applied to 69 residents to know the population socio-economic characteristics; An orthophotography, two digital elevation models, and information from the Ecuadorian Spatial Institute were used to elaborate: basic maps, a landslide susceptibility map using the matrix method, and two erosion susceptibility maps, one applying the universal equation method for soil loss (USLE) and the second through interferometry (multitemporal analysis), validated maps applying the confusion matrix, identifying areas susceptible to landslides and erosion. The surveyed population has 70% vulnerability to landslides and 67.4% to soil erosion. The proposed measures were: to strengthen local capacities for risk management to have resilient communities, strengthen local legal frameworks with technical support studies, and the variable risk management incorporated at the processes of land use and management and land planning.